Rheological properties of skeletal muscles in a Duchenne muscular dystrophy murine model before and after autologous cell therapy. (9th November 2021) - Zemła, Joanna; Iyer, Pavithra S.; Pyka-Fościak, Grażyna; Mermod, Nicolas; Lekka, Małgorzata
Graphical abstract: Abstract: Duchenne muscular dystrophy (DMD) is still an incurable muscle degenerative disease; thus, numerous studies focused on novel therapeutic approaches. However, a simple assay of muscle function restoration remains needed. Herein, we used an oscillatory shear rheometer to evaluate changes in rheological properties of mouse muscles ( tibialis anterior, TA) and their restoration upon autologous cell therapy by comparing the viscoelastic properties of normal, diseased and treated muscles. Amplitude sweep tests of muscle samples were performed under 20% compression over a range of shear strain between 0.01 and 2% and frequency of 1 rad/s. The samples were tested in plane-plane geometry and horizontal myofiber alignment. Typical linear viscoelastic region (LVER) patterns were found for each muscle type. For healthy muscles, a broad LVER between shear deformations (γ) of 0.013–0.62% was observed. The LVER of DMD mdx /SCID muscles was found at 0.14% to 0.46% shear deformation, and no shear dependence of storage ( G') and loss ( G") moduli at γ range changing from 0.034% to 0.26% was found for transplanted tissues. G'LVER and G"LVER moduli of healthy muscles were significantly higher than G'LVER and G"LVER of dystrophic tissues. Additionally, muscle resistance assessment by rheometer indicated that muscles transplanted with stem cells restored elastic properties to levels close to those of healthy muscles. Interestingly, histological staining and rheological data indicate that the loss factor is strongly related to structural changes of examined muscles.